Gene Expression Dynamics at the Neurovascular Unit During Early Regeneration After Cerebral Ischemia/Reperfusion Injury in Mice - Kestner, Roxane-Isabelle; Mayser, Franziska; Vutukuri, Rajkumar; Hansen, Lena; Günther, Stefan; Brunkhorst, Robert; Devraj, Kavi; Pfeilschifter, Waltraud (Frontiers in Neuroscience, 2020)
With increasing distribution of endovascular stroke therapies, transient middle cerebral artery occlusion (tMCAO) in mice now more than ever depicts a relevant patient population with recanalized M1 occlusion. In this case, the desired therapeutic effect of blood flow restauration is accompanied by breakdown of the blood-brain barrier and secondary reperfusion injury. The aim of this study was to elucidate short and intermediate-term transcriptional patterns and the involved pathways covering the different cellular players at the neurovascular unit after transient large vessel occlusion. To achieve this, male C57Bl/6J mice were treated according to an intensive post-stroke care protocol after 60 minutes occlusion of the middle cerebral artery or sham surgery to allow a high survival rate. After 24h or 7d, RNA from microvessel fragments from the ipsilateral and the contralateral hemispheres was isolated and used for mRNA sequencing. Bioinformatic analyses allowed us to depict gene expression changes at two timepoints of neurovascular post-stroke injury and regeneration. We validated our dataset by quantitative real time PCR of blood-brain barrier-associated targets with well-characterized post-stroke dynamics. Hence, this study provides a well-controlled transcriptome dataset of a translationally relevant mouse model 24h and 7d after stroke which might help to discover future therapeutic targets in cerebral ischemia/reperfusion injury.